Metode Penyelenggaraan Kuliah Studi Pasca Sarjana Post Pandemi: Mana Yang Lebih Memenuhi Kebutuhan Pasar? - Kurnia, Pepey Riawati (Research Center and Case Clearing House (RC-CCH) - Sekolah Tinggi Manajemen PPM, 2023)
The method of post-pandemic lecture delivery in postgraduate studies is an issue for educational institution management. Lectures will be delivered offline since the COVID-19 pandemic has subsided, and the conditions are recovering. Postgraduate students, especially working students, are protesting because they have to attend face-to-face lectures on weekdays for various reasons. This study aims to determine which postgraduate lecture delivery method meets the market needs (university students). The research method made use of Soft System Methodology (SSM). The FGD was conducted with twelve participants, classified into postgraduate students of Wijawiyata Management (full-time students), Young Executives (students with at least two years of work experience), and Executives (students with no less than five years of work experience). The research was conducted in March and April 2023. The results were analyzed using Role (clients, practitioners, and owners), Social (educational institutions and instructors), and Power (national policies and regulations) Analysis. This research shows that by rich picture and root definition, weekday online lectures and weekend (Saturday) offline lectures meet the market's needs and violate no Indonesian higher educational regulations. The findings also suggest that a combined lecture mode, offline and online, is more favorable to Master's degree students, hence the Indonesian government's rigorous encouragement for Distant Learning for various learning needs across the archipelago.